Corporate Social Responsibility and Firm Performance: Evidence from China - Jiang, Ziting (2020)
This paper aims to explore the relationship between corporate social responsibility and financial performance of listed enterprises in China. The sample is from 420 companies in 22 industries listed on the Shanghai Stock Exchange (SSE) and the Shenzhen Stock Exchange (SZSE) from 2009-2018. The OLS regression result shows that there is a negative relationship between CSR and CFP in Chinese listed companies. This paper argues three main reasons for the negative relationship. First, China's CSR process is still at a preliminary stage, so the initial cost paid for the implementation of CSR activities has not been made up by the benefits generated by the implementation of CSR. Second, there is an objective contradiction between the pursuit of profits and the satisfaction of all stakeholders in the management of Chinese enterprises. Third, although the CSR activities of public welfare undertakings have significant positive impact on the corporate image and reputation, there are defects in the management of charity undertaken by Chinese listed enterprises. As a result, Chinese enterprises should view and implement corporate social responsibility activities more critically. In view of the negative relationship, this paper puts forward some suggestions for the government and enterprises.